1985
DOI: 10.1007/bf00395153
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic adjustment in Spirulina platensis

Abstract: The filamentous cyanobacterium Spirulina platensis has been examined for salt tolerance and osmotic adjustment. Salinities up to 150% seawater had little effect on growth yield or photosynthetic O2 evolution; higher salinities were markedly inhibitory. Osmotic adjustment was achieved by the intracellular accumulation of the low-molecular-weight carbohydrate glucosyl-glycerol in response to increased external salinity: in fullstrength (100%) seawater glucosyl-glycerol accounted for approximately 5.0% of the dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…The spectrum (Fig. 1) ppm) that were highly reminiscent of those of O-a-D-glucopyranosyl-(1--+2)-glycerol (glucosylglycerol), a heteroside that accumulates in salt-stressed marine cyanobacteria (4,28,33,47). These nine resonances were the most intense of the spectrum, suggesting that the putative heteroside is the major organic solute accumulated in P. mendocina SKB70 grown at 0.8 M NaCl (Fig.…”
Section: Identificationmentioning
confidence: 97%
See 1 more Smart Citation
“…The spectrum (Fig. 1) ppm) that were highly reminiscent of those of O-a-D-glucopyranosyl-(1--+2)-glycerol (glucosylglycerol), a heteroside that accumulates in salt-stressed marine cyanobacteria (4,28,33,47). These nine resonances were the most intense of the spectrum, suggesting that the putative heteroside is the major organic solute accumulated in P. mendocina SKB70 grown at 0.8 M NaCl (Fig.…”
Section: Identificationmentioning
confidence: 97%
“…Other NMR parameters were as described previously (9). The compounds in the extracts were identified by comparing the chemical shifts in the spectrum with those of authentic compounds (L-glutamate, N-acetylglutaminylglutamine amide [NAGGN], a,a-D-trehalose, L-proline, and glycine betaine) or published values for glucosylglycerol (4,28,47). Osmolyte concentrations were determined by comparison of the peak heights with an internal standard (50 mM alanine) and were verified in some cases by high-pressure liquid chromatography (HPLC) or by amino acid analysis.…”
mentioning
confidence: 99%
“…In addition to glycogen, these molecules can serve as substrates for fermentation in cyanobacteria (22). Both glucosyl-glycerol and trehalose are present in Arthrospira platensis (29) and A. maxima CS-328 (8). It was shown that a 4-fold increase in carbohydrate content can be achieved by growing A. platensis in media supplemented with additional 1 M NaCl relative to no additional NaCl (28).…”
mentioning
confidence: 98%
“…This cyanobacterium tolerates salt stress up to 750 mM NaCl, about 1.5-fold the concentration in sea water (8,22,23,26). Accordingly, it can survive in lakes with high salt concentrations (12).…”
mentioning
confidence: 99%
“…Accordingly, it can survive in lakes with high salt concentrations (12). It has been reported that Spirulina accumulates trehalose and glucosyl glyceride when exposed to high salt concentrations (23). However, the molecular mechanism responsible for the accumulation of these compatible solutes has not yet been determined.…”
mentioning
confidence: 99%